Communicative Satisfaction Among Female Students of The Kindergarten Department (Journal of the College of Basic Education, 2025)
The present study aims to investigate communicative satisfaction among female students of the Kindergarten Department. To achieve this objective, the researcher employed the descriptive research method. The study population consisted of female students enrolled in the Kindergarten Department at Al-Mustansiriyah University / College of Basic Education, covering all four academic stages (first, second, third, and fourth years). A sample of 300 students was selected using a stratified random sampling technique with proportional distribution.To measure communicative satisfaction, the researcher adopted the scale developed by Al-Karkhi (2023), which is based on Hecht’s model and consists of 20 items. The psychometric properties of the scale items were verified through discriminative power and item-total correlation. The validity and reliability of the scale were also confirmed, with test-retest reliability reaching 0.87, while Cronbach’s alpha coefficient was 0.83.For statistical analysis, the researcher used Pearson’s correlation coefficient, t-test for one sample, t-test for two independent samples, Chi-square, and Cronbach’s alpha equation. The findings of the study revealed that the participants exhibited a high level of communicative satisfaction.